Prodromal Alzheimer’s Disease: Constitutive Upregulation of Neuroglobin Prevents the Initiation of Alzheimer’s Pathology - de Vidania, Silvia; Palomares-Perez, Irene; Frank-García, Ana; Saito, Takashi; Saido, Takaomi C.; Draffin, Jonathan; Szaruga, María; Chávez-Gutierrez, Lucía; Calero, Miguel; Medina, Miguel; Guix, Francesc X.; Dotti, Carlos G. (Frontiers in Neuroscience, 2020)
In humans, a considerable number of the autopsy samples of cognitively normal individuals aged between 57 and 102 years have revealed the presence of amyloid plaques, one of the typical signs of AD, indicating that many of us use mechanisms that defend ourselves from the toxic consequences of Aß. The human APP NL/F (hAPP NL/F) knockin mouse appears as the ideal mouse model to identify these mechanisms, since they have high Aß42 levels at an early age and moderate signs of disease when old. Here we show that in these mice, the brain levels of the hemoprotein Neuroglobin (Ngb) increase with age, in parallel with the increase in Aß42. In vitro, in wild type neurons, exogenous Aß increases the expression of Ngb and Ngb over-expression prevents Aß toxicity. In vivo, in old hAPP NL/F mice, Ngb knockdown leads to dendritic tree simplification, an early sign of Alzheimer’s disease. These results could indicate that Alzheimer´s symptoms may start developing at the time when defense mechanisms start wearing out. In agreement, analysis of plasma Ngb levels in aged individuals revealed decreased levels in those whose cognitive abilities worsened during a 5-year longitudinal follow-up period.